2014
DOI: 10.1021/am502250r
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Membrane Enrichment of Self-Assembling d-Peptides for Cell Surface Engineering

Abstract: We occasionally found that several self-assembling peptides containing D-amino acids would be preferentially enriched in cellular membranes at self-assembled stages while distributed evenly in the cytoplasma of cells at unassembled stages. Self-assembling peptides containing only Lamino acids distributed evenly in cytoplasma of cells at both self-assembled and unassembled stages. The self-assembling peptides containing D-amino acids could therefore be applied for engineering cell surface with peptides. More im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Wang et al developed self-assembling peptides with L- and D-amino acids (NBD-DFDFDYGLKKTETQ) and studied their biological functions in cells. Interestingly, the result demonstrated that the utilization of D-amino acids in self-assembling peptides boosts their cellular membrane localization [87]. D-amino acids were specially enriched in cellular membranes at self-assembled stages.…”
Section: Biomedical Applications Of Self-assembling Peptide-based mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al developed self-assembling peptides with L- and D-amino acids (NBD-DFDFDYGLKKTETQ) and studied their biological functions in cells. Interestingly, the result demonstrated that the utilization of D-amino acids in self-assembling peptides boosts their cellular membrane localization [87]. D-amino acids were specially enriched in cellular membranes at self-assembled stages.…”
Section: Biomedical Applications Of Self-assembling Peptide-based mentioning
confidence: 99%
“…However they were distributed uniformly in the cytoplasma of cells at unassembled stages. Wang et al [87] demonstrated the possibility of using such D-amino acid-based peptides to engineer cell surfaces.…”
Section: Biomedical Applications Of Self-assembling Peptide-based mentioning
confidence: 99%
“…This observation could in principle be exploited for the targeted delivery of a small molecule that has a specific site of action located at the cell membrane [50]. …”
Section: Drug Delivery Applicationsmentioning
confidence: 99%
“…Then, we discuss the less expected enzyme reactions of D-amino acid, especially highlighting the recent study of D-amino acids for enzyme-instructed self-assembly (EISA), which results in selectivity in potential anti-inflammatory or anticancer drug approaches. We hope that these discussions will help readers to appreciate the study of D-amino acids in achieving biostability(17, 18), investigating interactions between enzymes and D-peptides(19, 20), and improving bioactivities via the introduction of D-amino acids(21, 22). …”
Section: Introductionmentioning
confidence: 99%